2020
DOI: 10.1002/ajmg.a.61924
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia and respiratory infections in Down syndrome: A scoping review of the literature

Abstract: Pneumonia and respiratory infections impact infants and children with Down syndrome; pneumonia is a leading cause of mortality in adults with Down syndrome. We aimed to review the literature to evaluate gaps and address key questions. A series of key questions were formulated a priori to inform the search strategy and review process; addressed prevalence, severity, etiology, risk factors, preventive methods, screening, and financial costs, potential benefits or harms of screening. Using the National Library of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 61 publications
(105 reference statements)
1
27
0
4
Order By: Relevance
“…Prior to the COVID‐19 pandemic, we knew that patients with Down syndrome (DS) have differences in respiratory infections compared to the general population(Santoro et al, 2020). In childhood, pneumonia is the primary cause of hospital admissions for patients with DS, and lower respiratory tract infections accounted for 40% of admissions (Hilton, Fitzgerald, & Cooper, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the COVID‐19 pandemic, we knew that patients with Down syndrome (DS) have differences in respiratory infections compared to the general population(Santoro et al, 2020). In childhood, pneumonia is the primary cause of hospital admissions for patients with DS, and lower respiratory tract infections accounted for 40% of admissions (Hilton, Fitzgerald, & Cooper, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Review articles describe the pulmonary complications of DS during childhood, but devote a small section to pneumonia specifically (McDowell & Craven, 2011). Recently a literature review of 42 articles regarding pneumonia and respiratory infections in persons with DS underscored that there is an increased risk of pneumonia prevalence and severe illness among individuals with DS (Santoro et al, 2020). Strikingly, the literature review found that there are critical knowledge gaps in the prevention and screening of risk factors for pneumonia in the DS population as well as lack of infectious organism identification (Santoro et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Recently a literature review of 42 articles regarding pneumonia and respiratory infections in persons with DS underscored that there is an increased risk of pneumonia prevalence and severe illness among individuals with DS (Santoro et al, 2020). Strikingly, the literature review found that there are critical knowledge gaps in the prevention and screening of risk factors for pneumonia in the DS population as well as lack of infectious organism identification (Santoro et al, 2020). Researchers identified that literature is lacking regarding clinical indicators of pneumonia in persons with DS and in particular among living adults with DS (Santoro et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tido isso, estudos demonstraram que essa classe tem prevalência sete vezes maior de pneumonia e apresentam gravidade aumentada em infecções respiratórias, com maior risco de hospitalização, necessidade de terapia intensiva e uso de ventilação mecânica, quando comparados ao grupo controle. Em infecções pelo SARS-CoV-2, ensaios estimaram que a incidência de hospitalização na população com SD foi 8,9 vezes maior (IC: 4,00 -20,0) do que na população geral, para indivíduos entre 30 e 64 anos e esses pacientes eram, em média, 10 anos mais jovens do que o restante da população hospitalizada (Kantar et al, 2020;Santoro, 2020;Olsen, 2020).…”
Section: Resultsunclassified